2020
DOI: 10.31234/osf.io/q43ca
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Financial Homo Ignorans: measuring vulnerability to behavioral biases in household finance

Abstract: Understanding systematic differences in sound financial behavior between individuals is a key area for public policy and the possibility to tailor interventions to promote financial well-being. In this paper we develop and validate a concise 12 item questionnaire measuring individual’s vulnerability to behavioral biases in household finance – the Financial Homo Ignorans (FHI) Scale. We conduct two studies with general population samples (total N=2508) and show that the FHI scale can predict behavior in financi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 49 publications
0
24
0
1
Order By: Relevance
“…We measured financial ignorance using the Financial Homo Ignorans (FHI) scale (Barrafrem et al, 2020). Individuals were asked to state to what degree they agreed with a series of 12 statements on a scale from one to five.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We measured financial ignorance using the Financial Homo Ignorans (FHI) scale (Barrafrem et al, 2020). Individuals were asked to state to what degree they agreed with a series of 12 statements on a scale from one to five.…”
Section: Methodsmentioning
confidence: 99%
“…Previous research has identified multiple factors that affect financial well-being. Some of them include: (1) social and economic environment like macro-economic context, family wealth, access to education, and geographic location (Brüggen et al, 2017); (2) objective and subjective financial knowledge (Joo and Grable, 2004;Lind et al, 2020) (3) trait self-control (Strömbäck et al, 2020); and (4) information avoidance and financial ignorance (Barrafrem et al, 2020). The COVID-19 pandemic is having a great impact on the world's economic situation and thus constitutes a non-negligible part of the prevailing economic context.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Allgood and Walstad (2013) found that subjective financial knowledge was a stronger predictor of less costly practices in credit card use than objective financial knowledge. A possible mechanism is that people with high financial confidence might be less reluctant to avoid financial information, which could affect behavior (Barrafrem et al 2020). Beliefs about the extent of one's own knowledge might thus be as important (or more) as actual knowledge when it comes to sound financial behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has identified multiple factors that affect financial well-being; Some of them include: 1) social and economic environment like macro-economic context, family wealth, access to education, and geographic location (Brüggen, Hogreve, Holmlund, Kabadayi, & Löfgren, 2017) 2) objective and subjective financial knowledge (Joo & Grable, 2004;Lind et al, 2020); and 3) psychological factors (Barrafrem, Västfjäll, & Tinghög, 2020;Strömbäck, Lind, Skagerlund, Västfjäll, & Tinghög, 2017).…”
Section: Introductionmentioning
confidence: 99%